Penggunaan Model Pembelajaran Jigsaw Untuk Meningkatkan Maharah Qira’ah Siswa Kelas X MA NU Darul Islah Wonosobo - Uswatun Hasanah; Fatkhurrohman Fatkhurrohman; Rifqi Aulia Rahman (Institut Agama Islam Darusssalam Blokagung, 2022)
This study discusses learning Arabic, especially maharah qira’ah using the jigsaw learning model. The purpose of this study is to determine the learning process and result from the use of the jigsaw learning model in the maha>rah qira>’ah learning of class X MA NU Darul Islah Wonosobo student of the 2021/2022 school year. This research is a type of field research using a quantitative approach carried out at MA NU Darul Islah Wonosobo, with the type of experimental research, the research design uses quasi-experimental design, namely the existence of experimental classes and control classes. The method of data collection is carried out by methods of observation, interviews, documentation, and tests. The results of this study showed that: there was an increase in maharah qira’ah students of class X experiments being proven by a test gain of 0.466 with a moderate category. Then there is the difference in maharah qira’ah between classes that use the jigsaw learning model and those that do not use the jigsaw learning model with the calculation of data analysis obtained by researchers, namely 4.53. And the significance level of 5% and DK = (25+25)-2 = 48 obtained 2.01, and the level of significance of 1% obtained of 2.68. This result shows the value of the. Thus rejected and accepted. So there is a contrast between classes that utilize the jigsaw learning model and classes that don’t utilize the jigsaw learning model.